A 46, XX / 46, XY mosaicism or chimerism diagnosed by Karyotyping - Khan, Mansura; Moniruzzaman, Mohammad; Mohsin, Fauzia; Chowdhury, Ashesh K (Bangladesh Critical Care Journal, 2018)
The presence of both 46, XX and 46, XY cell lines in a person is a very rare condition which is known as either chimerism or mosaicism. These conditions usually determined in early childhood during investigation of ambiguous genitalia. Our case is probably the first such report case in our country. Our case was ten months aged child, born to non-consanguinous couple referred to Cytogenetics unit of Immunology Department of BIRDEM General Hospital for chromosomal analysis and Karyotyping with the chief complaint of right sided undescended testis. He was normal looking and playful, presenting complaint was small penis with abnormal urethral opening and absence of one testis since birth. His developmental milestones were normal and intelligence was average. There was no history of congenital and genetic diseases in their family. On examination of the external genitalia the following features were noticed: stretched penile length (SPL) 3.5 cm with penoscrotal hypospadiasis. Right sided testis was not palpable as undescended and left sided testis was palpable in scrotum , volume of which was 2 to 3 ml. Bangladesh Crit Care J September 2018; 6(2): 111-113